How much does the talocrural joint contribute to ankle dorsiflexion range of motion during the weight-bearing lunge test? A cross-sectional radiographic validity study - Smith, M. D.; Lee, D.; Russell, T.; Matthews, M.; MacDonald, D.; Vicenzino, B. (Journal of Orthopaedic & Sports Physical Therapy, 2019)
Background: Ankle dorsiflexion ROM is commonly measured during the weight-bearing lunge test (WBLT) as horizontal knee distance travelled or tibial inclination. These measures are assumed to represent talocrural dorsiflexion, yet have not been validated against radiographic images.